PERS DALAM WACANA HUKUM (Kajian tentang Kebebasan, Tanggungjawab, dan Deviasi Pers dalam Perspektif Hukum Islam dan Hukum Positif di Indonesia) - Idri Idri (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2010)
Abstract: Press takes an important role in expanding the country development, lastly it is not only lusty, free, and responsible but also it functions as an objective information disseminator, constrcutive social controll agent, public aspiration supplier, and to broaden public communication and participation. In brief, it needs to develop positive and harmony interaction among press, government, and society. The freedom of press in extending information to public has been one of the realizations of people soverignty, furthermore it becomes a significant aspect to establish life of civility on the basis of the priciples of democracy, justice, and law supremacy. On the whole, press independency might be a responsible freedom: toward government, public, and press council. Key Words: Pers, kebebasan pers, dan tanggung jawab pers